The Effect of the Ketogenic Diet on Aggression and Violence in Patients with Severe Mental Illness: A Systematic Review - Eleanor Rees; Gurpreet Kaler (BJPsych Open)
Aims: The aim of this systematic review was to explore the existing literature on the impact of the ketogenic diet on aggressive and violent behaviour in patients with serious mental illness and the potential mechanisms involved, with the hypothesis that the ketogenic diet can reduce aggression and violence in this patient population. The ketogenic diet has proven to be useful as a therapeutic to reduce some clinical symptoms of certain neurological and psychiatric conditions, so this review was interested to determine if there were any correlations in impacts on behaviour in similar patient populations.